Luminal bacterial antigen-specific CD4(+) T-cell responses in HLA-B27 transgenic rats with chronic colitis are mediated by both major histocompatibility class II and HLA-B27 molecules - Qian, Bi-Feng (Blackwell Science Inc, 2006)
Rats transgenic (TG) for the human major histocompatibility complex (MHC) class I HLA-B27 and β(2)-microglobulin genes develop chronic colitis under specific pathogen-free (SPF) but not sterile (germ-free, GF) conditions. We investigated the role of antigen-presenting molecules involved in generating immune responses by CD4(+) mesenteric lymph node (MLN) cells from colitic HLA-B27 TG rats to commensal enteric micro-organisms. All TG MLN cells expressed HLA-B27. A higher level of MHC class II was expressed on cells from TG rats, both SPF and GF, compared to non-TG littermates. In contrast, rat MHC class I expression was lower on TG than non-TG cells. Both TG and non-TG antigen presenting cells (APC) pulsed with caecal bacterial antigens induced a marked interferon-γ (IFN-γ) response in TG CD4(+) T lymphocytes but failed to stimulate non-TG cells. Blocking MHC class II on both TG and non-TG APC dramatically inhibited their ability to induce TG CD4(+) T cells to produce IFN-γ. Blocking HLA-B27 on TG APC similarly inhibited IFN-γ responses. When the antibodies against MHC class II and HLA-B27 were combined, no APC-dependent IFN-γ response was detected. These data implicate both native rat MHC class II and TG HLA-B27 in CD4(+) MLN T-cell IFN-γ responses to commensal enteric microflora in this colitis model.